Economic Burden of Treatment‐Resistant Depression Among Patients Hospitalized for Major Depressive Disorder in the United States. Issue 2 (11th October 2019) - Lin, Jay; Szukis, Holly; Sheehan, John J.; Alphs, Larry; Menges, Brandy; Lingohr‐Smith, Melissa; Benson, Carmela
Abstract : Objectives: This study aimed to evaluate hospital length of stay (LOS) and cost as well as readmission risk and the associated economic burden among patients hospitalized for treatment‐resistant and non–treatment‐resistant major depressive disorder. Methods: Adult patients with a primary hospital discharge diagnosis of major depressive disorder were identified from the Premier Hospital Database (January 1, 2012–September 30, 2015). Patients were stratified into two cohorts: those whose hospital treatment was suggestive of treatment‐resistant depression and those with non–treatment‐resistant depression. Hospital LOS and cost during the initial admission and readmissions rates, LOS, and cost within the 6‐month follow‐up were compared between cohorts with a propensity score–matched sample. Results: After matching, 45, 066 patients were included in each cohort. For index hospitalizations, mean hospital LOS was longer (7.4 vs. 5.9 days, p<0.001) and mean hospital cost higher (8, 681 vs. 6, 632, p<0.001) for patients with treatment‐resistant depression vs. non–treatment‐resistant depression. Rates for all‐cause (24.4% vs. 20.0%, p<0.001), major depressive disorder–related (17.0% vs. 13.3%, p<0.001), and suicidal ideation/suicide attempt–related (12.8% vs. 9.5%, p<0.001) readmissions were higher for patients with treatment‐resistant depression. Mean LOS and total hospital costs per patient for readmissions were also greater for patients with treatment‐resistant depression vs. non–treatment‐resistant depression. Correspondingly, the combined hospital cost (index hospitalization+all‐cause readmissions) was greater for patients with treatment‐resistant depression (12, 370 vs. 9, 429, p<0.001). Conclusions: Treatment‐resistant depression was associated with substantial economic burden among patients hospitalized for major depressive disorder. More‐effective treatment and care for this patient population may reduce the hospital burden of patients with treatment‐resistant depression.